THE POLITICS OF BANK SUPERVISION - Sukarman, Widigdo (Journal of Indonesian Economy and Business, 2011)
The bank supervision function and efficacy of monetary policy are often a trade-off for the central bank. An increasingly integrated financial system and the occurrence of bank crises during the 1980s raised the question: are central banks efficient in overseeing banks and is there a requirement for integrated supervision, either under the central bank or separate? The debate among academics and policymakers has never been settled without the guarantee that one alternative will ensure optimal bank supervision. This development has led to periodic changes in the form of supervision chosen. As the basic economic choice has been unsatisfactory, this study approaches the problem using path-dependence theory, which observes historical factors of bank development as well as the constellation of domestic politics in choosing these alternatives.Keywords: path-dependence, bank supervision, politics, country-specific